Carbon with different functionalities as a hydrogen transport layer in ruthenium promoted Fischer -Tropsch catalysts - Buthelezi, Thuli Innocentia (My University, 2019)
Fischer-Tropsch synthesis (FTS) is the catalytic production of hydrocarbons from synthesis gas (carbon monoxide and hydrogen) which is derived from biomass, coal or oil. Cobalt (Co) is a highly active and selective metal catalyst used in FTS. Two ways of improving the activity of a Co catalyst are (i) by adding a Ru promoter and (ii) by using defective carbon (nitrogen doped carbon) as a support. A Ru promoter increases the activity of a Co catalyst by reducing a Co precursor at lower temperature through hydrogen spillover, which involves the transfer of hydrogen from a Ru surface to a Co precursor surface. A nitrogen doped carbon support provides stability to the Co nanoparticles and prevents particle agglomeration. Furthermore, the electron-rich nitrogen groups can enhance the electronic conductivity of the carbon support thus potentially improving hydrogen spillover. In this study we used nitrogen doped hollow carbon spheres (NHCSs) as a carbon support for Ru (0.5%) promoted Co (10% and 15%) catalysts. The Co catalysts were synthesized by the hard templating method, using polystyrene as the hard template. The use of the NHCSs as a support allowed for the separation of the locations of the Co metal and the Ru metal, thus enabling hydrogen spillover studies. The study also explored the effect of varying synthesis parameters such as annealing time and the type of nitrogen doping (in situ nitrogen doping and post nitrogen doping) used on the hydrogen spillover effect. The supported catalysts were structurally characterized using a range of techniques; TEM, SEM, PXRD, TGA, Raman, BET, XPS and CHNS analyses. The reducibility of the catalysts was assessed using TPR analysis and in situ PXRD analysis. In preliminary studies, the activity of the catalysts was tested under low temperature FTS conditions. TEM studies showed that polystyrene was a good and stable template for synthesizing the NHCSs as the formed carbon support was spherical and had a hollow morphology. The NHCSs had average diameters of 380 nm and shell thickness of 40 nm. The NHCSs was a good support and the hollow core effectively stabilized the Co and Ru metal nanoparticles as they were obtained in small sizes with narrow particle size distributions (Co@NHCS, 6.2 nm; Co@NHCS@Ru, 6.2 nm catalyst; Co-Ru@NHCS 4.5 nm). CHNS analysis and XPS analysis confirmed the successful presence and incorporation of N-atoms (5% - 7%) within the carbon matrix by a post doping method. Furthermore, XPS analysis confirmed that pyridinic-N, pyrrolic-N, quaternary-N and oxidised-N were present within the carbon matrix. BET analysis showed the surface area of the NHCSs to be 188 m2/g and those of the Co catalysts to be lower (143 m2/g - 102 m2/g) due to the blockage of the pores by nanoparticles and by the bulky nitrogen groups. All the catalysts have a mesoporous shell (2.5 nm - 4.7 nm). PXRD studies showed that the carbon was amorphous in nature (broad XRD peak; 22.3 °) and that the cubic spinel phase Co3O4 was formed. TGA studies showed that the NHCSs were more stable against oxidation than supported Co catalysts and this was attributed to the ability of Co3O4 nanoparticles to catalyse the oxidation of the carbon support. The TPR analysis revealed that the direct contact between Co and Ru (Co-Ru@NHCS) promoted a primary hydrogen spillover effect (Co3O4 →Co, 269 °C) whereas indirect contact (Co@NHCS@Ru) slightly enhanced the secondary hydrogen spillover effect (Co3O4 →CoO, 347 °C; CoO→Co, 420 °C). In situ PXRD studies were in agreement with the TPR studies showing that the presence of direct contact between Co and Ru gave the highest degree of reduction (99 %) compared to indirect contact (97 %) and the unpromoted (59 %) Co catalyst. The high degree of reduction was due to the hydrogen spillover effect. Furthermore, the presence of Ru improved the relative abundance of the Cohcp phase. The TEM images of the Co catalysts supported inside the in situ nitrogen doped hollow carbon support (Co@NHCSI) showed good dispersion. The catalyst also showed the lowest oxidation (TGA analysis) and improved Co oxide reduction (TPR analysis) due to the nitrogen defects being present throughout the carbon matrix. The preliminary results of the Fischer-Tropsch synthesis process showed that the unpromoted Co@NHCS catalyst had a higher CO conversion and catalytic activity than the promoted Co-Ru@NHCS catalyst. The low activity of the Co-Ru@NHCS catalyst could be attributed to low mass diffusion issues.
A thesis submitted to the School of Chemistry, Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the Degree of Masters of Science, February, 2019